Retrospective cost analyses of EPA regulations: a case study approach. Issue 2 (June 2014) - Kopits, Elizabeth; McGartland, Al; Morgan, Cynthia; Pasurka, Carl; Shadbegian, Ron; Simon, Nathalie B.; Simpson, David; Wolverton, Ann
Abstract: EPA has conducted several ex post assessments of regulatory compliance costs, with the ultimate goal of identifying ways to improve ex ante cost estimation. The work to date has culminated in four case studies that examine five regulations using a common conceptual framework. The standardized framework provides a systematic way to investigate key drivers of compliance costs to see if judgments can be made about why and how ex ante and ex post estimates of costs differ. In addition to describing this conceptual framework, we describe the criteria used to select the rules to be analyzed, summarize the main hypotheses for why ex ante and ex post cost estimates may differ and discuss some of the challenges encountered in conducting these ex post analyses.